POLITICAL EMPOWERMENT OF WOMEN IN AUSTRALIA: AN ANALYSIS - Musharaf Rubab; Adnan Nawaz; Ghulam Mustafa; Muhammad Imran (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Australia stands first among the states of the world to give most of the women to voting right. Australia is also the leading state which promotes policy regarding gender parity. But it does not mean that women representation is ideally achieved in Australia. Irrespective of all the efforts by the governmental and private levels, Australian women are still behind men political fields as most of the key positions in the political offices are being held by men. There might be lack of coordination in efforts in this field as individual and group efforts can be seen for women emancipation in political, social and economic sphere are not producing the desired results. This article attempts to elucidate the facts about women participation in Australian politics. The role of women in legislature and in political parties depicts a promising scenario but requires a lot of improvement to gain the objective of gender equality in Australian Politics.